PERANCANGAN SISTEM INFORMASI AKUNTANSI PENJUALAN TUNAI BERBASIS WEBSITE PADA PERUSAHAAN UMUM DAERAH AMAN MANDIRI KOTA TIDORE KEPULAUAN - Rahmadani; Herman Karamoy; Christian Datu (Universitas Sam Ratulangi, 2023)
This research was conducted to design a website-based accounting information system for cash sales to fulfill the needs of the Perumda-AM in overcome the weaknesses of the manual recording system. The research is a development research uses a qualitative approach. The research subject is Perumda-AM and the object in this research is cash sales accounting information system. Data were collected through interviews, documentation and observation. The system development method in this study uses a system development life cycle with stages of system analysis, system requirements analysis and system feasibility analysis. System design includes database modeling using database tables, process modeling using flowcharts, and interface modeling using form design, input design and output design. Sales accounting information system design using MySQL and PHP software. The design made is expected to facilitate more automatic and accurate recording and calculations that support the business sustainability of Perumda-AM's performance by utilizing the latest technology.